2015
DOI: 10.14237/ebl.6.2.2015.365
|View full text |Cite
|
Sign up to set email alerts
|

A Look from the Inside: MicroCT Analysis of Burned Bones

Abstract: MicroCT imaging is increasingly used in paleoanthropological and zooarchaeological research to analyse the internal microstructure of bone, replacing comparatively invasive and destructive methods. Consequently the analytical potential of this relatively new 3D imaging technology can be enhanced by developing discipline specific protocols for archaeological analysis. Here we examine how the microstructure of mammal bone changes after burning and explore if X-ray computed microtomography (microCT) can be used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Numerous studies are to be found in the literature based on vibrational spectroscopy techniques, namely Raman (34,39,(61)(62)(63) and Fourier transform infrared (FTIR) (28,34,35,46,50,54,64), X-ray powder diffraction (XRD) (33,50,57,59,(65)(66)(67), X-ray fluorescence (XRF) (37,38,(68)(69)(70), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) (43,55,57,71), scanning electron microscopy (SEM) (15,43,57,(72)(73)(74)(75), nuclear magnetic resonance (NMR) and magnetic resonance imaging (MRI) (15,76), and computational tomography (CT) (77)(78)(79).…”
Section: Methodologiesmentioning
confidence: 99%
“…Numerous studies are to be found in the literature based on vibrational spectroscopy techniques, namely Raman (34,39,(61)(62)(63) and Fourier transform infrared (FTIR) (28,34,35,46,50,54,64), X-ray powder diffraction (XRD) (33,50,57,59,(65)(66)(67), X-ray fluorescence (XRF) (37,38,(68)(69)(70), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) (43,55,57,71), scanning electron microscopy (SEM) (15,43,57,(72)(73)(74)(75), nuclear magnetic resonance (NMR) and magnetic resonance imaging (MRI) (15,76), and computational tomography (CT) (77)(78)(79).…”
Section: Methodologiesmentioning
confidence: 99%
“…By applying a range of analytical methods and imaging modalities, studies have demonstrated that subtle and complex changes occur within the bone structure as a result of thermal exposure (e.g. Boschin et al 2015;Thompson 2015a & b;Ellingham et al 2015Ellingham et al , 2016Cascant et al 2017). Crucially, it has been argued that these changes can be correlated with specific burning conditions, and hence allow for the contextual interpretation of the event itself.…”
Section: Recent Advances In the Study Of Burned Bonementioning
confidence: 99%
“…Morphological alterations seen in the burnt vertebrae and otoliths included changes in colour due to carbonisation (in line with Nicholson 1995), a loss of increment clarity, and a reduction in weight. The reduction of sample weight/density, or "shrinkage" (Shipman et al 1984), is likely due to the thermal denaturation of the collagen component of the structure at temperatures as low as 60ºC (Richter 1986), while burning has been shown to affect bone microstructure significantly at about 400ºC (Boschin et al 2015). Given that otolith or vertebrae weight are commonly used to estimate fish size (Disspain et al 2012;Gabriel et al 2012;Quinn and Deriso 1999), the use of burnt samples would likely underestimate the fish's actual size, thereby resulting in inaccurate fisheries baseline data or an underestimate of meat yield.…”
Section: Res 25mentioning
confidence: 99%